Efeito do envelhecimento cronológico e da prática regular de exercícios físicos sobre a aptidão cardiorrespiratória de mulheres idosas - Kohler, Renan (2014)
Purpose: This study analyzed the effects of chronological aging and the exercise regular practice (ERP) on cardiorespiratory fitness (CRF) in older women. Methods: This descriptive ecological study with longitudinal design conducted its first evaluation in 2005 and the second in 2011, in 78 participants. The ERP defined the groups: Inactive (I), Insufficient-Active (IA), and Sufficient-Active (SA). The six-minute walking test measured the CRF. A MANOVA with repeated-measures was used with the purpose to verify a time and group main effects on CRF (p<0.05). Results: Sample means classified the participants as low socioeconomic level and overweight. MANOVA demonstrated an time (F1,74=30,134; p<0.05) and group main effects (F2,74=3,729; p<0.05), without interaction (F2,74=0.811; p>0.05). Post hoc analysis indicated that the time main effect was significantly between all groups (I: t=3,786, p<0.05; IA: t=2,597, p<0.05; SA: t=3,191, p<0.05); and the group main effect was significantly only between the I and SA groups in the second evaluation (First evaluation: F2,76=1,712; p>0.05; Second Evaluation: F2,77 = 3,239; p<0.05, post hoc Tukey: group I vs AS = p<0.05). A lower decline of CRF was found in SA group (8,0%), following by IA (10,3%) and I (14,3%). Conclusion: The results of this study indicated that older adult women who practice exercise regularly had the lower decline in CRF when compared to those who are inactive. It suggests that the ERP at recommended levels for health-benefits can attenuate the effect of aging on the CRF.